Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Quick on the Draw terhadap Keaktifan Belajar pada Pembelajaran PAI-BP Kelas VIII di SMP Negeri 1 Sungai Pua - Melati, Rima; Arifmiboy, Arifmiboy; Ilmi, Darul; Afrinaldi, Afrinaldi (YASIN, 2024)
This research is motivated by the fact that students' learning activity is still relatively low. The aim is to find out whether the average learning activity of participants is above 75 and whether there is a significant influence on PAI-BP class VIII learning on the subject matter "Usury in Buying and Selling and Accounts Payable". This research is experimental research with a static group comparison design. The population was all students in class VIII of SMP Negeri 1 Sungai Pua and the sampling technique used probability sampling with class VIII 1 as the experimental class and VIII 3 as the control class. Data was collsected using questionnaires and documentation, then analyzed using the T-test, namely the one sample t-test and the independent t-test. It was found that the average learning activity of students using the Quick On The Draw cooperative learning model was above 75, confirmed by the results of the one sample t-test, namely sig.(2-tailed) 0.002<0.05. The tcount value is 3.468>ttable 2.064. The next finding is that there is a significant influence of using the Quick On The Draw cooperative learning model on learning activity, confirmed by the results of the independent sample t-test, namely the Sig value. (2-tailed) 0.000 < 0.05 and has an average difference (Mean Difference¬) 13.14000.